1989
DOI: 10.1002/1097-4679(198911)45:6<957::aid-jclp2270450622>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of relaxation techniques on trait anxiety: A meta-analysis

Abstract: Hand and computer searches located studies on the effects of relaxation techniques on trait anxiety. Effect sizes for the different treatments (e.g., Progressive Relaxation, EMG Biofeedback, various forms of meditation, etc.) were calculated. Most of the treatments produced similar effect sizes except that Transcendental Meditation had significantly larger effect size (p <.005), and meditation that involved concentration had significantly smaller effect. Correlations with effect size were calculated for many v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(131 citation statements)
references
References 13 publications
(7 reference statements)
11
115
0
5
Order By: Relevance
“…Therefore, it is possible to conclude that Meditación Fluir can also be effective in improving academic performance and self-concept, at the same time as reducing the levels of anxiety in a sample of adolescent students. These results are in agreement with those found by other studies that show the beneficial effects of practicing meditation on academic performance (Beaucheim et al, 2008;Chang & Hierbert, 1989;Crason et al, 1991;León, 2008;Sugiura, 2003), and relate them to improvement in self-concept (Trumbulls, & Norris, 1982;Van der Berg & Mulder, 1976), and lowered anxiety levels (Barnes et al, 2001;Beaucheim et al, 2008;Epply et al, 1989;Kabat-Zinn et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible to conclude that Meditación Fluir can also be effective in improving academic performance and self-concept, at the same time as reducing the levels of anxiety in a sample of adolescent students. These results are in agreement with those found by other studies that show the beneficial effects of practicing meditation on academic performance (Beaucheim et al, 2008;Chang & Hierbert, 1989;Crason et al, 1991;León, 2008;Sugiura, 2003), and relate them to improvement in self-concept (Trumbulls, & Norris, 1982;Van der Berg & Mulder, 1976), and lowered anxiety levels (Barnes et al, 2001;Beaucheim et al, 2008;Epply et al, 1989;Kabat-Zinn et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In our study thirty percent respondents felt that TM was based on scientific evidence, while 25% felt it was safe and efficacious than other relaxation techniques. David W. Orme-Johnson conducted Meta analysis of 600 research papers of randomized controlled trials on safety and efficacy of TM and concluded that the TM technique produces greater reductions in anxiety than mindfulness or other meditation and relaxation practice [19][20][21][22][23][24] . It was reported from this meta-analysis that other relaxation techniques did not have as great an effect in reducing neuroticism or autonomic stress reactivity and did not increase frontal and central alpha EEG coherence as TM practice [25] .…”
Section: Fig 1: Source Of Information Of Tm To the Respondents Discumentioning
confidence: 99%
“…Many studies have shown reduction of blood pressure after meditation. [25][26][27] There was a significant reduction of DBP in current study after practicing balasana for 90 days. Brownstein and Dembert [28] also observed in their study, on mild hypertensive patients who had unsuccessful control with thiazides that there was significant reduction in DBP after yoga therapy while Sundar et al [29] found that the reduction in DBP is more than that of SBP.…”
Section: Discussionmentioning
confidence: 99%